HIV stigma, resilience and depressive symptoms among older adults living with HIV in rural Namibia. Issue 3 (2nd July 2020) - Kalomo, Eveline Ndinelao; Jun, Jung Sim; Lee, Kyoung; Kaddu, Mgori Nuru
Abstract : In sub-Saharan Africa, HIV-positive older adults aged 50 years and older experience complex psychosocial issues in addition to dealing with their HIV status and the ageing process. This study focused on the association between HIV stigma, resilience, and depressive symptoms among 147 older adults from the Oshana and Ohangwena health facilities in rural Namibia. The study used the hierarchical multivariate regression analysis method to reveal that there was a positive association between HIV stigma (negative self-perceptions) and depression as well as a negative relationship between resilience and depression. In addition, being female and higher education were protective factors, and disclosure of HIV status was a risk factor to predict depressive symptoms among the target population. In order to reduce HIV stigma and enhance resilience among older adults living with HIV in Africa, this study suggests the need to develop evidence-based interventions to increase coping strategies and resilience.